E-moderating the key to teaching and learning online - Salmon, Gilly (New York : Routledge, 2011)
"The third edition of this best-selling guide has been fully updated and addresses the many technological changes that have taken place in the field of online teaching and learning since 2004. Interest in online teaching continues to grow, yet one thing remains constant: the key role of the e-moderator in ensuring the quality and success of online learning. Offering a practical approach and easy accessibility, Moderating is the perfect users manual to working effectively in the virtual world.New topics include:Updates of all literature, key terms, case studies and projectsFresh new examples for how the 5 stage model has been successfully used around the worldTips for e-moderating in Virtual Reality platforms such as Second LifeTips for e-moderating in Social Networking SitesNew illustrative examples from the latest All Things in Moderation coursesUpdated applications for training school teachersFully updated Resources for Practitioners SectionHigher Education practitioners, professional developers, trainers, and online instructional designers will find this classic book is a must-have resource for anyone teaching online or developing online courses. It is also an appropriate text for students enrolled in Educational Technology and Distance Education Masters and PhD programs"--
pt. 1. Concepts and cases -- pt. 2. Resources for practicioners.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Teaching -- Computer network resources; Computer-assisted instruction; Distance education; Electronic books